Efektivitas Penegakan Hukum dan HAM di Indonesia Terhadap Kasus Pembunuhan Munir Dalam Memperjuangkan Hak Asasi Manusia - Qothrun Nada Zahrotun Nabila (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Indonesia can be said to be a country of law and a country that adheres to democratic principles. As a country that adheres to democratic principles, it should be able to place supreme power in the hands of the people. The correlation between these powers cannot be separated from the basic rights inherent in every human being. However, in reality we still often encounter violations of human rights. One of them is the Munir murder case, which until now has not yet received justice. Munir is classified as a human rights defender who has greatly contributed to protecting the common people. This has become a risk if you join the ranks of activists as human rights defenders like Munir, namely threatening the security and welfare of your life. Because the government's arguments are not in line with them Because the government's arguments are not in line with theirs, so it can give rise to bad behavior and intentions if the opposing party does not accept it.